Progress in urban greenery mitigation science – assessment methodologies advanced technologies and impact on cities - Santamouris, Mat; Ban-Weiss, George; Osmond, Paul; Paolini, Riccardo; Synnefa, Afroditi; Cartalis, Constantinos; Muscio, Alberto; Zinzi, Michele; Morakinyo, Tobi Eniolu; Ng, Edward; Tan, Zheng; Takebayashi, Hideki; et al. (Journal of Civil Engineering and Management, 2018)
Urban greenery is a natural solution to cool cities and provide comfort, clean air and significant social, health and economic benefits. This paper aims to present the latest progress on the field of greenery urban mitigation techniques including aspects related to the theoretical and experimental assessment of the greenery cooling potential, the impact on urban vegetation on energy, health and comfort and the acquired knowledge on the best integration of the various types of greenery in the urban frame. Also to present the recent knowledge on the impact of climate change on the cooling performance of urban vegetation and investigate and analyse possible technological solutions to face the impact of high ambient temperatures.